Macrophage Related Chronic Inflammation in Non-Healing Wounds - Li, Meirong; Hou, Qian; Zhong, Lingzhi; Zhao, Yali; Fu, Xiaobing (Frontiers in Immunology, 2021)
Persistent hyper-inflammation is a distinguishing pathophysiological characteristic of chronic wounds, and macrophage malfunction is considered as a major contributor thereof. In this review, we describes the origin and heterogeneity of macrophages during wound healing, and compared the macrophage function in healing and non-healing wounds. We consider extrinsic and intrinsic factors driving wound macrophage dysregulation, and review systemic and topical therapeutic approaches for the restoration of macrophage response. Multidimensional analysis in highlighted through the integration of various high-throughput technologies, used to assess the diversity and activation states as well as cellular communication of macrophages in healing and non-healing wound. This research fills the gaps in current literature and provides the promising therapeutic interventions for chronic wounds.